Nuclear localised more sulphur accumulation1 epigenetically regulates sulphur homeostasis in arabidopsis thaliana - Huang, Xin-Yuan; Wirtz, Markus; Hell, Rüdiger (PLoS Genetics, 2016)
Author Summary Sulphur is an essential element for all living organisms including plants. Plants take up sulphur from the soil mainly in the form of inorganic sulphate. The uptake of sulphate and assimilation of sulphur have been well studied. However, the regulation of sulphur accumulation in plants remains largely unknown. In this study, we characterize the high leaf sulphur mutant more sulphur accumulation1 (msa1-1) and demonstrate the function of MSA1 in controlling sulphur accumulation in Arabidopsis thaliana. The MSA1 protein is localized to the nucleus and is required for the biosynthesis of S-adenosylmethionine (SAM) which is a universal methyl donor for many methylation reactions, including DNA methylation. Loss of function of MSA1 reduces the SAM level in roots and affects genome-wide DNA methylation, including the methylation of sulphate transporter genes. We show that the high sulphur phenotype of msa1-1 requires elevated expression of the sulphate transporter genes which are differentially methylated in msa1-1. Our results suggest a connection between sulphur homeostasis and DNA methylation that is mediated by MSA1.